Pemberdayaan Kader dalam Program Perencanaan Persalinan dan Pencegahan Komplikasi (P4K) dengan Aplikasi Pronalin-cek - Budiarti, Yati; Yuliastuti, Santi; Irianti, Bayu (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Kesehatatan Kemenkes Palembang, 2025)
Maternal mortality remains high in Indonesia, presenting a major challenge to achieving the Sustainable Development Goals (SDG) target of 70 deaths per 100,000 live births by 2030. In 2023, the Maternal Perinatal Death Notification (MPDN) system recorded 4,129 maternal deaths, with leading causes including hypertensive disorders of pregnancy (801 cases), haemorrhage (741 cases), heart disease (232 cases) and other causes (1,504 cases). Despite a national obstetric complication‐management coverage of 94.16% and 91.7% in West Java, the prevention of complications remains critical. In Tasikmalaya in 2023, the maternal mortality ratio was 192.1 per 100,000 live births, of which 27% were due to hypertensive disorders or haemorrhage and 46% due to infection, cardiovascular disease and anaemia. The Birth Planning and Complication Prevention Programme (P4K) is a strategy to accelerate maternal and neonatal mortality reduction by improving access to and quality of antenatal care, skilled birth attendants, postpartum care, emergency obstetric care, referral and family planning. P4K empowers pregnant women, their families and communities to recognise risk and danger signs and plan for safe delivery. Digital education media such as the “Pronalin-Cek” application enable broader, flexible delivery of P4K information by health workers or health cadres. Given that cadres are community‐based and closely connected to families, empowering them via Pronalin-Cek offers an effective approach. This community service project in the Kelurahan Mulyasari – Tamansari sub‐district involved 16 cadres (n = 16) being trained to use the Pronalin-Cek application as a P4K educational tool. The method comprised: (1) capacity building of cadres with a pre-test, P4K & application training, and post-test, (2) mentoring of digital literacy and use of the application, and (3) ongoing monitoring and evaluation. Results showed the average knowledge score increased from 13.50 to 16.18 (p = 0.00; SD 1.59 to 1.22). Most cadres were housewives (87.5%) with education ranging from elementary to high school. These findings suggest that empowering health cadres with digital P4K tools can significantly enhance their knowledge and potential contribution to maternal health services. It is recommended to expand the programme, conduct long‐term evaluations of cadre behaviour and maternal health outcomes, and adopt quasi-experimental designs to assess the impact on mothers and newborns.